2014
DOI: 10.1016/j.neuron.2013.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Structured Synaptic Connectivity between Hippocampal Regions

Abstract: The organization of synaptic connectivity within a neuronal circuit is a prime determinant of circuit function. We performed a comprehensive fine-scale circuit mapping of hippocampal regions (CA3-CA1) using the newly developed synapse labeling method, mGRASP. This mapping revealed spatially nonuniform and clustered synaptic connectivity patterns. Furthermore, synaptic clustering was enhanced between groups of neurons that shared a similar developmental/migration time window, suggesting a mechanism for establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
165
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(184 citation statements)
references
References 41 publications
(69 reference statements)
16
165
0
Order By: Relevance
“…The size and location of these dendritic compartments are not fixed and can dynamically change according to the activation and input pattern Behabadi et al, 2012;Jadi et al, 2012;Major et al, 2013). Recent studies support the notion of anatomical and functional clustering of synapses to dendritic compartments both during development and learning (Fu et al, 2012;Takahashi et al, 2012;DeBello et al, 2014;Druckmann et al, 2014;Cichon and Gan, 2015), in line with the possibility that dendritic branchlets may serve as key plasticity and storage elements during learning (Mel, 1992;Poirazi and Mel, 2001;Chklovskii et al, 2004).…”
Section: Compartmentalized Plasticity Mechanismsmentioning
confidence: 74%
“…The size and location of these dendritic compartments are not fixed and can dynamically change according to the activation and input pattern Behabadi et al, 2012;Jadi et al, 2012;Major et al, 2013). Recent studies support the notion of anatomical and functional clustering of synapses to dendritic compartments both during development and learning (Fu et al, 2012;Takahashi et al, 2012;DeBello et al, 2014;Druckmann et al, 2014;Cichon and Gan, 2015), in line with the possibility that dendritic branchlets may serve as key plasticity and storage elements during learning (Mel, 1992;Poirazi and Mel, 2001;Chklovskii et al, 2004).…”
Section: Compartmentalized Plasticity Mechanismsmentioning
confidence: 74%
“…In a different piece of work from the same serial dataset the directional selectivity of individual amacrine dendrites looked to be arranged in a way that was incompatible with random contacts . In hippocampus, support for the idea that connectivity was not explicable simply by proximity has also been obtained (Mishchenko et al, 2010;Druckmann et al, 2014). The previous results do not explicitly test the degree to which actual proximity of each individual axon to all the postsynaptic sites in a volume explains the connectivity patterns observed.…”
Section: Discussionmentioning
confidence: 91%
“…24, 2015; findings and demonstrated that dendrites extend the computational capacity of a single neuron (Cazé et al, 2012(Cazé et al, , 2013. Recent experimental evidence has shown that excitatory synapses distribute non-randomly on dendrites and can form synaptic clusters (Takahashi et al, 2012;Druckmann et al, 2014;Kleindienst et al, 2011). We examine here whether we can employ the spatial distribution of excitatory synapses to implement stimulus selectivity.…”
Section: Introductionmentioning
confidence: 92%